O-265 Luteinizing hormone is able to protect reproductive health in cancer patients. (30th June 2022) - Lamsira, H.K; Marcozzi, S; Vicenti, R; Centonze, C; Rella, F. Di; De Felici, M; Serracchioli, R; Fabbri, R; Klinger, F.G
Abstract: Study question: Is luteinizing hormone (LH) able to protect ovarian follicles against cyclophosphamide (CPM)-induced damage in women? Summary answer: LH significantly reduces primordial follicle (PMF) loss in ovarian cortical strips cultured in vitro with phosphoramide mustard (PM), the active metabolite of CPM. What is known already: Cancer therapies are cause of premature ovarian insufficiency (POI) in female patients, since they induce a severe reduction of PMFs. For this reason, several compounds have been analyzed as adjuvant therapies to protect the ovarian reserve without interfering with cancer treatment on tumor cells. We recently demonstrated the protective effect of LH against ovotoxicity induced by PM and cisplatin on the ovary of prepuberal and adult mice. These results suggest the possibility to use LH prior or in concomitance with anticancer drugs in order to preserve oocytes in human patients, therefore preventing the early onset of menopause and/or infertility. Study design, size, duration: Ovarian cortical tissues were collected from nine patients (age ± SD: 15.33 ± 4.50) who have cryopreserved their tissue before receiving anticancer treatment. For each patient, ovarian cortical strips were thawed and randomly assigned to the experimental conditions: Control (CTRL), PM and PM+LH. LH was added 1 hour before the treatment with PM. Samples were analyzed after 8, 16, 24 and 48 hrs of treatment. Participants/materials, setting, methods: Ovarian cortial strips were placed onto culture plate insert and cultured for a maximum of 48 hours, in αMEM with 10% Serum Substitute Supplement with/out 200mIU/ml LH and/or 10μM PM. The samples were processed for: - Histology, for PMFs and primary follicles (PFs) analysis; - Immunohistochemistry, for the expression of protein involved in DNA damage, apoptosis and follicle activation; - Real-Time PCR, for the expression of apoptotic and inflammation related genes. Main results and the role of chance: The follicle density in the untreated group varied from 233.03 to 3420.27 PMFs/mm3 between the nine patients analysed. Relative follicular density (%) was performed to analyse statistical differences between the groups. Relative PMFs density (%) was significantly reduced in PM vs CTRL either after 24 and 48 hrs, while this reduction was significantly counteracted by LH (24 hrs: CTRL=76.19±2.12; PM = 44.95±5.06; PM+LH=73.97±11.64. 48 hrs: CTRL=66.47±3.96; PM = 36.76±3.96; PM+LH=55.74±8.72). To investigate the mechanism underlying the observed effects, the expression of markers involved in DNA damage (gH2AX), apoptosis (Cleaved caspase 3, NOXA, PUMA), follicle activation (p-AKT, FOXO3a), cell cycle arrest (p21, Ki67), and inflammation (IL1β, TNFα) were analysed. The results showed that LH did not prevent DNA damage induced by PM, since gH2AX positive oocytes were seen both in PM and PH+LH group at 16h; at 24hrs however we observed a downregulation of the gH2AX expression in the PH+LH group (PM@ 100% vs PM+LH@35%). LH also counteracts the activation of chemotherapy-induced apoptotic processes, by reducing the levels of pro-apoptotic factors such as NOXA, PUMA and CC3, and follicles activation lowering AKT-FOXO3a signaling axis. Moreover, PM treatment creates a proinflammatory microenvironment, as shown by increased IL1β and TNFα gene expression, partially counteracted by LH pretreatment. Limitations, reasons for caution: Experiments are carried out in vitro ; the functionality of the cortex in xenografts should be evaluated. Careful evaluation of which patients might use this protector is needed. Wider implications of the findings: These findings demonstrate that LH is able to reduce PMFs loss in human ovarian cortex exposed to PM. These results encourage thinking about the use of the hormone as a ferto-protector agent in clinical trials to prevent the premature onset of menopause and/or infertility in women undergoing anticancer treatments. Trial registration number: not applicable